2009
DOI: 10.1039/b911083f
|View full text |Cite
|
Sign up to set email alerts
|

Hollow mesoporous carbon spheres—an excellent bilirubin adsorbent

Abstract: Hollow mesoporous carbon spheres (HMCSs) were used for the first time as a bilirubin adsorbent, which showed an extraordinarily high bilirubin adsorption capacity as compared with commercial activated carbon for haemoperfusion, high bilirubin adsorption selectivity and negligible hemolytic activity. The results are very attractive and promising for blood purification applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 181 publications
(111 citation statements)
references
References 22 publications
1
108
1
1
Order By: Relevance
“…No apparent pathological changes were observed using the hematoxylin-eosin staining protocol [48]. Because they lack surface Si-OH, MCBs did not induce the RBC hemolysis observed for traditional mesoporous silica, indicating high hemocompatibility [47,90,93,94]. Although the preliminary biocompatibility results are encouraging, the biosafety evaluation of MCBs is still at the preliminary stage.…”
Section: Biocompatibility Of Mcbsmentioning
confidence: 97%
See 2 more Smart Citations
“…No apparent pathological changes were observed using the hematoxylin-eosin staining protocol [48]. Because they lack surface Si-OH, MCBs did not induce the RBC hemolysis observed for traditional mesoporous silica, indicating high hemocompatibility [47,90,93,94]. Although the preliminary biocompatibility results are encouraging, the biosafety evaluation of MCBs is still at the preliminary stage.…”
Section: Biocompatibility Of Mcbsmentioning
confidence: 97%
“…We demonstrated that HMCNs could act as a clinical adsorbent for bilirubin [90], which can cause crippling, athetoid cerebral palsy and even death if overproduced [91]. Various absorbents such as activated carbon, chitosan, resins, and porous TiO 2 have been employed as adsorption materials in hemoperfusion columns to remove bilirubin from the blood [90]. HMCNs with large hollow interiors and well-defined mesoporous shells (Figs 13a and b) were elaborately synthesized using silica core/ mesoporous silica shell core/shell-type templates and exhibited substantially higher bilirubin-adsorption capacity (304 mg g −1 ) compared with commercial activated carbon (70 mg g −1 ) and CMK-3 mesoporous carbon (198 mg g −1 ).…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In a healthy human body, the concentration of bilirubin in the blood is basically kept at a relatively constant level. However, when the liver's function is impaired, the bilirubin cannot be adequately excreted and thus accumulates in the organism.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the liver's function is impaired, the bilirubin cannot be adequately excreted and thus accumulates in the organism. 1 The presence of excess bilirubin may cause hepatitis, jaundice, brain damage, and even death in severe cases. 2 Many techniques, such as hemodialysis, phototherapy, and hemoperfusion, have therefore been applied to remove bilirubin from hyperbilirubinemic human plasma for reducing bilirubin level to normal range.…”
Section: Introductionmentioning
confidence: 99%